Characteristics of the education and training process for the growth of Chinese Olympic champions - Hu, H. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
PURPOSE: Years of systematic and deliberate training is the cornerstone of improving athletes sports performance and achieving Olympic success.Education and training are crucial components in the journey to becoming an Olympic champion. METHODS: Using questionnaire*interviews and literature review*this study analyzed the key data for the growth of 175 Olympic champions. Under the overall guidance of the Department of Policies and Regulations of the Chinese General Administration of Sports, and with the help of the sports system of various provinces and cities across the country, a total of 251 questionnaires were issued and 175 valid questionnaires were recovered, with an effective response rate of 69.72%. In terms of specific statistical methods, for most of the quantitative data conforming to the normal distribution, the mean ± SD is used, and the 95% CI is calculated, and the independent sample t test is used for the comparison between these groups; quantitative data for small samples and it does not conform to the normal distribution, the median (interquartile range) is used to indicate, and the non-parametric Mann-Whitney U test is used for comparison between groups. In addition, the one-variable linear regression equation and its fitting line based on least squares verify the linear relationship between the training start age and the training start period. RESULTS: The research found that successful Olympic athletes do not necessarily come from privileged backgrounds or inherit their athletic talents. Centralized class teaching was the main method of education for champions and they have a longer college and postgraduate education compared to the average. The average time it takes to become an Olympic champion is 13.85 years, with the youth training period being the longest and having significant gender and event group differences. The start of training at a young age within a reasonable range leads to success, but premature specialization may not be beneficial. CONCLUSION: The research provides valuable insights for the cultivation of elite athletes